A Short Cist Burial at Kilkeddan Farm, Campbeltown, Argyll & Bute. Issue 1 (March 2016) - McLaren, Dawn; Wilson, Donald; Engl, Rob; Duffy, Alan; MacSweeney, Kathleen; Sheridan, Alison; Troalen, Lore; Carruthers, Graeme; Humble, Jamie
Abstract : AOC Archaeology Group undertook the excavation of a previously unknown Bronze Age cist, located in a field close to Kilkeddan Farm, Argyll & Bute, during September 2005 under the Historic Scotland call-off contract for human remains. The cist was found to contain poorly surviving unburnt human skeletal remains along with a finely decorated tripartite Food Vessel and a flint knife. The incomplete and fragmentary condition of the skeleton suggests that the human remains were disarticulated at the time of deposition. Radiocarbon dates obtained from the human bone and associated charcoal confirms an early Bronze Age date for the burial.